Revitalizing Ancestral Values through Technology: Using Wayang Kulit to Engage Gen Z in Cultural and Educational Innovation - Kasinathan, Vinothini; Rubasundram, Geetha A.; Fuu, Wong Chai (Journal of Ecohumanism, 2024)
“Wayang Kulit” is a cultural heritage that combines art, storytelling, education and creativity. Although it has many charms, the lack of awareness as well as opportunity to witness this art and the perceived indifference amongst the younger generation is slowing diminishing the impact of the Wayang Kulit especially in line with ancestral values and education. This research aimed to assess if technology and education using the Wayang Kulit could be an attractive learning tool for Gen Z to apply ancestral culture and values within a modern context. In order to make it more attractive and relevant from a technology perspective, the participants selected were undergraduates from Asia Pacific University of Technology and Innovation (APU) pursuing courses in Multimedia and Games Development. The participants were required to create a short video between 2 to 3 minutes embedding the art of “Wayang Kulit” using popular stories linking it to the Sustainable Development Goals (SDG) for a competition known as “Videre Lumina”. The participants were also interviewed to understand further their experience and whether the “Wayang Kulit” could potentially be a strong asset in educational innovation. This qualitative study used the Social Learning Theory (SLT) and analyzed the videos and interviews using Pragmatist Thinking and Interpretative Phenomenological Analysis. The results reflected positive feedback towards “Wayang Kulit” and the stories behind it. The students were also enthusiastic with the learning process and the ability to communicate their story-telling skills from a multitude of ways including expressing themselves digitally through the stories, backgrounds, music, characters and the puppets. The link to culture was especially noted when participants of different backgrounds portrayed the same characters as hero’s or villain’s depending on their culture or heritage stories. Therefore, the “Wayang Kulit” is definitely an intangible asset that should be continued and celebrated as its benefits and charm can impact education, values and be used as a social engineering tool. The use of technology also provides further opportunities to expand the opportunity to watch this art and further create awareness and appreciation for its value.